Territory of Alaska / Treasury Department, U.S. Coast and Geodetic Survey (U.S. Coast and Geodetic Survey, 1898)
Relief shown by hachures and spot heights.; Includes inset map of the Aleutian Islands. Color; 1:1,200,000